Nursing Care for Post PCNL Patients With Acute Pain Through Foot Massage in the Urology Surgery Room at General Ahmad Yani Metro Hospital - Iman, Firda Garbo; Wardoyo, Eko; Sugiarto, Sugiarto (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objectives: Management of acute pain in post-operative PCNL (Percutaneous Nephrolithotomy) patients is essential to support optimal recovery and improve patients' quality of life. One effective non-pharmacological method to manage pain is foot massage therapy, which provides a relaxing effect and helps reduce pain intensity. This scientific work aims to describe nursing care using foot massage interventions in post-PCNL patients with complaints of acute pain. Methods: This research design is a case study, with the research subject being a patient who was treated in the urology surgery room at General Ahmad Yani Metro Hospital. Foot massage intervention was carried out for two consecutive days, each for 20 minutes each session. The techniques used included effleurage and petrissage movements on the patient's foot area, designed to relieve pain and improve blood circulation. Results: The results showed a decrease in pain intensity in patients after foot massage therapy, from scale 7 to scale 4 within 30 minutes post intervention. Conclusion: This effect shows that foot massage is effective in reducing acute pain in post-PCNL patients, so it can be recommended as a complementary pain management method.